Phytosomes as a Possible Nano-Delivery System for Enhanced Oral Bioavailability and Hepatoprotective Activity of Indigofera barberi - Thatipally Rajeshwar; Ananda Kumar Chettupalli (The Bioscan, 2025)
Indigofera barberi Gamble, a Fabaceae plant, has traditionally been used to treat skin, renal, and liver problems. Documented phytochemicals include glycosides, steroids, tannins, phenolic compounds, and flavonoids. Its low bioavailability and solubility hinder GI absorption. This study sought to improve Indigofera barberi extract bioavailability by making the ethanolic extract more soluble and absorbable. We optimized Indigofera barberi-loaded phytosomes utilizing solvent evaporation. This study developed IBPCs-NPs, a novel phytosome-nanosuspensions for IB shielding, to improve IB bioavailability and hepatoprotection. In in vivo pharmacokinetic studies, the IBPCs-NP formulation had higher plasma concentration and in vitro dissolution rate. IBPCs-NPs also demonstrated stronger hepatoprotective effects in pharmacodynamic studies. Crystalline variation and IB-phospholipid interactions are also physicochemical features of optimized IBPCs-NPs. The synthesised IB phytosomes were cylindrical, smooth-surfaced, and distinct, with a diameter of 332.52 ± 1.54 nm. According to dissolving trials, the enhanced IB phytosomal formulation released silymarin faster and in greater proportions than pure silymarin, with better water solubility ( 360 µg/mL). The optimized silymarin phytosomal formulation normalized antioxidant enzymes and helped CCl4-intoxicated cells. In in vivo experiments, it protected the liver from CCl4-induced hepatotoxicity in rats. The optimized phytosomal formulation enhanced oral silymarin bioavailability compared to pure silymarin. This was shown by six-fold systemic bioavailability. Whole phytosomes may increase water-insoluble phyto-constituent oral bioavailability as phospholipid-based nanocarriers.